Biliary and Pancreatic Dysgenesis in Mice Harboring a Mutation in Pkhd1 - Gallagher, Anna-Rachel (American Society for Investigative Pathology, 2008)
Autosomal recessive polycystic kidney disease is a hereditary fibrocystic disease that involves the kidneys and the biliary tract. Mutations in the PKHD1 gene are responsible for typical forms of autosomal recessive polycystic kidney disease. We have generated a mouse model with targeted mutation of Pkhd1 by disrupting exon 4, resulting in a mutant transcript with deletion of 66 codons and expression at ∼30% of wild-type levels. Pkhd1(del4/del4) mice develop intrahepatic bile duct proliferation with progressive cyst formation and associated periportal fibrosis. In addition, these mice exhibit extrahepatic manifestations, including pancreatic cysts, splenomegaly, and common bile duct dilation. The kidneys are unaffected both histologically and functionally. Fibrocystin is expressed in the apical membranes and cilia of bile ducts and distal nephron segments but is absent from the proximal tubule. This pattern is unchanged in orthologous models of autosomal dominant polycystic kidney disease due to mutation in Pkd1 or Pkd2. Mutant fibrocystin in Pkhd1(del4/del4) mice also retains this expression pattern. The hypomorphic Pkhd1(del4/del4) mouse model provides evidence that reduced functional levels of fibrocystin are sufficient for cystogenesis and fibrosis in the liver and pancreas, but not the kidney, and supports the hypothesis of species-dependent differences in susceptibility of tissues to Pkhd1 mutations.